2017
DOI: 10.3389/fimmu.2017.00255
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota, Immune Subversion, and Chronic Inflammation

Abstract: Several host-adapted pathogens and commensals have evolved mechanisms to evade the host innate immune system inducing a state of low-grade inflammation. Epidemiological studies have also documented the association of a subset of these microorganisms with chronic inflammatory disorders. In this review, we summarize recent studies demonstrating the role of the microbiota in chronic inflammatory diseases and discuss how specific microorganisms subvert or inhibit protective signaling normally induced by toll-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 149 publications
0
47
0
5
Order By: Relevance
“…In the present study, the frequency of obesity was significantly higher in the rosacea group than in the control group, which probably accounts for the significantly higher frequency of metabolic and cardiovascular disorders in the rosacea group. Additionally, oral and gut microbiome dysbiosis are associated with systemic inflammation leading to atherosclerosis . An earlier study in 60 rosacea patients and 50 gender‐ and age‐matched controls observed that coronary artery disease risk factors were significantly more common in the rosacea patients than in the controls .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the frequency of obesity was significantly higher in the rosacea group than in the control group, which probably accounts for the significantly higher frequency of metabolic and cardiovascular disorders in the rosacea group. Additionally, oral and gut microbiome dysbiosis are associated with systemic inflammation leading to atherosclerosis . An earlier study in 60 rosacea patients and 50 gender‐ and age‐matched controls observed that coronary artery disease risk factors were significantly more common in the rosacea patients than in the controls .…”
Section: Discussionmentioning
confidence: 99%
“…19 In the present study, the frequency of obesity was significantly higher in the rosacea group than in the control group, which probably accounts for the significantly higher frequency of metabolic and cardiovascular disorders in the rosacea group. Additionally, oral and gut microbiome dysbiosis are associated with systemic inflammation leading to 20 An earlier study in 60 rosacea patients and 50 gender-and age-matched controls observed that coronary artery disease risk factors were significantly more common in the rosacea patients than in the controls. 21 A nationwide casecontrol study conducted in Taiwan that included 33,553 rosacea patients and 67,106 age-and gender-matched controls noted that dyslipidemia, hypertension, and coronary artery disease were significantly associated with rosacea.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that this is more reflective of the exposures of human infants. We have an increasing appreciation for the effects of the microbiome on the ability of the immune system to respond to challenge [4042]. The microbiome established in newborns is the result of exposure in the birth canal as well as from environmental encounters in the first days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, several of these host-adapted Gram-negative bacteria that express immune-evasive lipid A are associated with increased risk of autoimmune disease (Vatanen et al 2016), type I diabetes, atherosclerosis (Erridge et al 2007b; Slocum et al 2014), and allergic disorders in childhood and adulthood (Grönlund et al 2000; Ogra and Welliver 2008). A role of lipid A variants is to allow a bacterium to evade TLR4 and promote chronic inflammation and these variants appear to act through dysregulation of both innate and adaptive immune responses (Kramer and Genco 2017). …”
Section: The Importance Of Proteobacteria To Immune Education In Earlmentioning
confidence: 99%